Peran Orientasi Pasar dan Strategi Diferensiasi terhadap Loyalitas Pelanggan dan Kinerja Perusahaan - Diah Permata; Sri Kemala (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
The increasingly intense competition in the coffee shop industry requires companies to understand customer needs and create unique competitive advantages to ensure business sustainability. The objective of this study is to analyze the influence of market orientation and differentiation strategies on customer loyalty and company performance, as well as to test the mediating role of customer loyalty. The study employs a quantitative approach using a survey method targeting 250 coffee shop customers in West Sumatra, selected through purposive sampling. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that market orientation has a positive and significant effect on customer loyalty and company performance. Differentiation strategies also have a positive and significant effect on customer loyalty and company performance. Customer loyalty was found to have a positive effect on company performance and to mediate the relationship between market orientation and differentiation strategies on company performance. The study’s conclusion affirms that improved company performance can be achieved through strengthening market orientation, implementing effective differentiation strategies, and continuously building customer loyalty.